Distributed Self-Healing for Resilient Network Design in Local Resource Allocation Control - Kim, Jaeho; Hayashi, Yukio (Frontiers in Physics, 2022)
Many infrastructure networks are considered as the backbone of our society, however increasing disasters and terrors give serious damages to energy, water, communication, and transportation systems. In this paper, we propose a distributed self-healing method for the damaged networks whose original structure is extremely vulnerable scale-free. For reconstructing a sustainable network, the key ideas of our method are ring formation and enhancing loops by adding the resource of healing links between low degree nodes inspired from the state-of-the-arts edge rewiring method. In emulating a healing algorithm asynchronously, we show that the reconstructed network has both higher robustness and efficiency than the ones by the conventional self-healing methods. Our distributed self-healing will be useful as a basic framework for sustainable network reconstruction.